Proposal of a human talent development policy for the improvement of service quality in a sample of three-five star-hotels in Lima and Huanuco - Calderon Cahue, Johny José (2018)
The present research sought to establish how human talent development policies should be oriented towards the improvement of hotel service quality. The methodology was with a correlative analysis, applied to simultaneous samples of the zones in Lima and Huánuco; taking as sample workers from Lima and Huánuco, who were evaluated through instruments that were responsible for appreciating our two variables of the present study, the first of them the independent, the talent development policy, the second one, the dependent, the quality of the hotel service, obtaining a correlation index of 0.981 pts.; that is, 98.1%, with an index of freedom of 019 or 1.9%; with which we validate our alternative hypothesis; which we end up that a greater application of the human talent development policies oriented will improve the quality of hotel service in the case studies, which can be manifested through a regular perception of the indicators of both variables.